THE EXPOSURE EFFECT OF PPKM LEVEL 4 NEWS ON KOMPAS.COM ON ATTITUDES TO COMPLY WITH HEALTH PROTOCOLS - Rayni Delya Hafni; Elisabeth Nugrahaeni Prananingrum; Maulina Larasati Putri; Vera Wijayanti Sutjipto (Profetik: Jurnal Komunikasi, 2023)
The Covid-19 pandemic in Indonesia has not yet stopped and to overcome it the government has made a policy, namely PPKM (Enforcement of Community Activity Restrictions) Level 4 on (July 26 – August 23, 2021) which applies in several regions in Indonesia, one of which is the Province of DKI Jakarta. With PPKM Level 4, various online media, one of which is Kompas.com, is to report it. Therefore, this study aims to analyze the effect of exposure to PPKM Level 4 news on Kompas.com for the period 26 July – 23 August 2021 on the attitude toward carrying out health protocols in UNJ Communication Science students. In this study, the researcher uses the uses and gratifications theory, with quantitative research and survey methods by distributing questionnaires to 77 respondents. The results of this study show that H0 is rejected and Ha is accepted, which indicates that PPKM news exposure is Level 4 The period of July 26 – August 23, 2021 on Kompas.com has an influence on the attitude toward obeying health protocols in UNJ Communication Science students.